STRENGTHENING DIVERSITY VALUES THROUGH PATRIOTISM-BASED CHARACTER EDUCATION IN ELEMENTARY SCHOOL - Radina Mahdiana Mujib Riyanto; Zainal Hakim; Khodimul Wahid; Zaharah Hussin (STAI Ma'had Aly Al-Hikam Malang, 2026)
Patriotism Education plays an important role in shaping students’ character and strengthening diversity values from an early age. In the context of Indonesia’s multicultural society, elementary education is expected to foster attitudes of tolerance, respect for differences, and cooperation among students. This study aims to describe the process of instilling diversity values through Patriotism Education learning at Madrasah Ibtidaiyah. This research employed a qualitative approach using a case study design conducted at MI Miftahul Huda Tongas, Probolinggo. The participants included the school principal, fourth-grade teacher, and fourth-grade students. Data were collected through observations, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that diversity values are integrated into Patriotism Education materials, active learning methods, and daily school activities. Teachers apply various strategies such as group discussions, role-playing, educational games, and audiovisual media to enhance students’ understanding of cultural, ethnic, religious, and linguistic diversity in Indonesia. School support and teacher role modeling also contribute significantly to fostering students’ attitudes of mutual respect, tolerance, empathy, and cooperation. However, several challenges remain, including limited learning resources, insufficient teacher training, and inconsistent reinforcement of diversity values within the family environment. This study concludes that Patriotism Education learning can effectively strengthen diversity values and contribute to the development of students as tolerant citizens with Pancasila character.